Transcriptome and methylome of the supraoptic nucleus provides insights into the age-dependent loss of neuronal plasticity - Thompson, Derick; Odufuwa, Abiodun E.; Brissette, Catherine A.; Watt, John A. (Frontiers in Aging Neuroscience, 2023)
The age-dependent loss of neuronal plasticity is a well-known phenomenon that is poorly understood. The loss of this capacity for axonal regeneration is emphasized following traumatic brain injury, which is a major cause of disability and death among adults in the US. We have previously shown the intrinsic capacity of magnocellular neurons within the supraoptic nucleus to undergo axonal regeneration following unilateral axotomization in an age-dependent manner. The aim of this research was to determine the age-dependent molecular mechanisms that may underlie this phenomenon. As such, we characterized the transcriptome and DNA methylome of the supraoptic nucleus in uninjured 35-day old rats and 125-day old rats. Our data indicates the downregulation of a large number of axonogenesis related transcripts in 125-day old rats compared to 35-day old rats. Specifically, several semaphorin and ephrin genes were downregulated, as well as growth factors including FGF’s, insulin-like growth factors (IGFs), and brain-derived neurotrophic factor (BDNF). Differential methylation analysis indicates enrichment of biological processes involved in axonogenesis and axon guidance. Conversely, we observed a robust and specific upregulation of MHCI related transcripts. This may involve the activator protein 1 (AP-1) transcription factor complex as motif analysis of differentially methylated regions indicate enrichment of AP-1 binding sites in hypomethylated regions. Together, our data suggests a loss of pro-regenerative capabilities with age which would prevent axonal growth and appropriate innervation following injury.